(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2012)
The total discharge of the Neka River (Iran) groundwater flow and its deep laid distribution have been determined on the basis of applying water balance, biolocation and geophysical methods of research. The places of boreholes have been established for groundwater withdrawal for the purpose of water supply.